2017
DOI: 10.1111/obr.12641
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lifestyle interventions for preventing harmful weight gain among young adults from lower socioeconomic status and ethnically diverse backgrounds: a systematic review

Abstract: The incidence of overweight and obesity are increasing with each successive generation of young adults. Associated co-morbidities will emerge at an earlier age unless weight gain is prevented. Evidence has demonstrated young adults (aged 18-35 years) from low socioeconomic and ethnically diverse backgrounds are at greater risk of overweight or obesity, yet it is unclear how to effectively intervene in this population. This systematic review aimed to assess the effectiveness of lifestyle interventions conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 84 publications
(388 reference statements)
1
29
0
Order By: Relevance
“…Our IPD meta‐analysis, however, showed no differential effects on BMI across socio‐economic groups for workplace health promotion programmes. This is in line with several reviews on public health interventions that showed that the majority of the included studies on the prevention of unhealthy behaviour or obesity did not have differential effects across socio‐economic groups 5–7,9,10,14,15,33 . However, as unhealthy behaviours and obesity are more prevalent in workers in low SEP, the need for effective interventions for these workers remains of eminent importance.…”
Section: Discussionsupporting
confidence: 81%
“…Our IPD meta‐analysis, however, showed no differential effects on BMI across socio‐economic groups for workplace health promotion programmes. This is in line with several reviews on public health interventions that showed that the majority of the included studies on the prevention of unhealthy behaviour or obesity did not have differential effects across socio‐economic groups 5–7,9,10,14,15,33 . However, as unhealthy behaviours and obesity are more prevalent in workers in low SEP, the need for effective interventions for these workers remains of eminent importance.…”
Section: Discussionsupporting
confidence: 81%
“…It is clear, however, that a significant segment of research and theory about the development of OW/OB has been directed to a more ecological approach through a consideration of social, ethnic, evolutionary, cultural, or macroenvironmental factors such as politics and food marketing and that these have important influences on child OW/OB. 3,19,21,22,65,91,92,211,235,329,330 We acknowledged these macroenvironmental factors in Figure 1, but did not directly examine evidence in relation to their contributions to parent behavior such as feeding practices and cognitions (eg, about child weight, food and diet).…”
Section: Limitationsmentioning
confidence: 99%
“…Other electronic interventions for weight gain prevention conducted in young adults but without a sleep component report mixed success. Previously, it has been reported that among 30 interventions in 18‐ to 35‐year‐olds, 20 resulted in weight loss . Of these 30 programs tested, 15 were technology mediated and six of these were effective .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that among 30 interventions in 18‐ to 35‐year‐olds, 20 resulted in weight loss . Of these 30 programs tested, 15 were technology mediated and six of these were effective . The six that prevented weight gain included three with personal contact either face‐to‐face or brief phone coaching .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation